Potential Trump Tariff Conflict in 2025 and Its Implications for International Trade - Abukari, Yakubu; Saluja, Rajni (Theoretical and Practical Research in Economic Fields; Vol 16 No 4 (2025): TPREF Special Issue, Volume XVI, Issue 4(36), Winter 2025, 2025)
This study examines the dynamics of Trump's tariff strategy, as well as its long-term impacts on the global economy, trade networks, and inflation trajectories through 2025 and 2030. Using updated statistics and economic models, the analysis shows how protectionist trade policies, which were designed to address trade imbalances, have instead contributed to supply-chain regionalization, a slowdown in global growth, and persistent inflationary pressures. Empirical evidence from 2020 to 2025 shows that the tariff war raised the U.S. trade deficit and delayed the expansion of international commerce. The report offers three forward-looking scenarios - Technological Protectionism, Strategic Recalibration, and Bloc Polarization - in order to assess different policy paths. The results show that while recalibration through selective liberalization could restore modest growth and inflation stability, sustained tariff rises could reduce global GDP growth to 1.7% and trade volume by more than 10% by 2030. Policy proposals emphasize the need to revitalize multilateral trade governance, coordinate monetary and fiscal policies, and promote regional production resilience through sustainable and unique tariff regimes. The research predicts that globalization will eventually shift toward "managed interdependence" by fusing strategic autonomy with cooperative frameworks. These findings provide an essential basis for policymakers, economists, and international organizations seeking to develop flexible policies for an increasingly fragmented global trade landscape.